Karakteristik Pembakaran dan Emisi Gas Buang Mesin Diesel Stasioner Berbahan Bakar Campuran Solar (Cinnamon Oil dan Basil Oil) - Sianturi, Roy Lamrun; Melinda, Tiara; Malau, Rinaldo Hasudungan (Program Studi Teknik Mesin, Universitas HKBP Nommensen, Medan, 2026)
The depletion of fossil fuels and stringent emission regulations demand renewable additives that enhance diesel combustion while reducing pollutants. This study experimentally investigates the combustion characteristics and exhaust emissions of diesel blended with cinnamon oil and basil oil as dual additives in a single-cylinder stationary diesel engine. Essential oils were mixed with diesel at 5%, 10%, and 15%, either singly or in combination, and tested at 1500 rpm under varying loads (0–100%). Results showed that the dual additive blend at 10% (DCB10) yielded the best performance, reducing CO and HC emissions by up to 40.9% and 32.1%, respectively, compared to neat diesel. However, NOx emissions increased by 8.5% due to higher combustion temperatures and oxygen availability. The synergistic effect of cinnamon oil's low viscosity and basil oil's antioxidant properties improved atomization and oxidation kinetics, leading to more complete combustion. Despite the NOx trade-off, the net environmental benefit is positive, positioning dual essential oil blends as promising bio-additives for cleaner diesel operation.